Dietary selenium supplementation: its impact on growth, microbiota, antioxidant capacity, and immunity in Inner Mongolian cashmere goats - Wen, Yuliang; Xiang, Yuping; Shao, Yajing; Wang, Tao; Liang, Jianyong; Liu, Bin; Wu, Tiecheng (Frontiers in Veterinary Science, 2025)
Selenium (Se) is an essential trace element in the animal body that plays a crucial role in regulating antioxidant defense, immune response, and reproductive performance, contributing significantly to overall animal health. This study aimed to investigate the effects of dietary yeast selenium added to the feed on growth performance, antioxidant capacity, immune response, and rumen microbes of Inner Mongolian cashmere goats. A total of 18 male Inner Mongolian cashmere goats (47.1 ± 1.1 kg, 24 months of age) were selected and randomly divided into two groups, the normal feeding group (CON group) and the yeast selenium supplementation group (0.4 mg/d, Se group) (n = 9 in each group) for 30 days of the experiment. The results showed that the average daily weight gain in the Se group was significantly higher than that in the CON group (p < 0.05). In addition, the levels of glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), immunoglobulin IgA, and IgG in the blood and semen in the Se group were significantly higher than those in the CON group (p < 0.05). Dietary supplementation with yeast selenium mainly increased the abundance of Bacteroidales_RF16_group, p-251-o5, UCG-004, and UCG-010 in the rumen (p < 0.05). Spearman’s correlation analysis showed that Bacteroidales_RF16_group, Bacteroidales_RCG-004, and Bacteroidales_RCG-010 significantly affected the rumen microbiota and fermentation parameters and significantly increased the antioxidant and immune capacity of plasma and seminal plasma (p < 0.05). This study provides data to support the use of supplemental yeast selenium for the healthy breeding of cashmere goats.